Women in the Covid-19 Pandemic: the Psychosocial State of Female Students in Poland. - Izabela Kochan; Anna Walczak; Joanna Lewczuk (Studia z Teorii Wychowania)
The global pandemic-induced crisis has caused the differences that exist between the sexes in many areas of life to become more extreme. Apart from its influence on mental health, the necessity to adjust to the obligation of social distancing has also influenced the possibilities of students’ development as regards relationships. It has also limited their ability to earn money, which directly affects one’s economic status and other related areas such as the availability of healthcare, etc. This study, which aims to present the psychosocial state of women who have been studying in Poland during the pandemic, shows that it is women, more than men, who have experienced the changes caused by the pandemic, both in the context of how they function and their fears. Life satisfaction amongst female students depends largely on their economic and material independence, and any hardships experienced influence, more often than in the case of men, the emotions that are dominant in women. The results of the study clearly show that in the long run establishing a network of psychological support for women will be necessary as a response to their psychosocial health, which has worsened during the pandemic. Additionally, educated people who, in these difficult times, have not had the possibility to earn money or have had to accept jobs below their competencies (which may also significantly affect their life satisfaction), will be in need of support.